Assess the knowledge and utilization of Dr. Muthulakshmi Reddy maternity benefit scheme among women receiving antenatal services in selected urban health centre at Chennai. - MRS. G.BHUVANESWARI (International Journal of Pharma and Bio Sciences, 2017)
Pregnancy is the vital event in life of a woman. It needs special attention from the time of conception to the postnatal period. During that period mother need more medical supervision and health services. Currently the Government is implementing many health interventions for antenatal mothers to provide quality care. The maternal health benefits encouraging mother to choose for institutional deliveries. The main aim of the study to assess theknowledge andutilization of Dr. Muthulakshmi Reddy maternity benefit scheme amongwomen receivingantenatal services in selectedurban health centre at chennai. Themain objective of the study is to assess the demographic variables and assess the knowledge onutilization among the mothers receiving antennal service in selectedurban health centre at Chennai. Descriptive research designs was adopted in this study, 60 sample were selected by theNon probability convenience sampling technique. The present study was conducted to assess the knowledge and utilization of maternity benefit schemeamong antenatal mothers. In that majority of the samples had the 30% adequate knowledge, 17%mothers had inadequate knowledge, 30% mothers were had moderate adequate knowledge regardingthe maternal benefit scheme. So we are the students and staffs of community health nurse department , should give the information about the benefits schemes through IEC activities and communicating the information to the public.